2012
DOI: 10.1088/0256-307x/29/3/038904
|View full text |Cite
|
Sign up to set email alerts
|

Mandelbrot Law of Evolving Networks

Abstract: Degree distributions of many real networks are known to follow the Mandelbrot law, which can be considered as an extension of the power law and is determined by not only the power-law exponent, but also the shifting coefficient. Although the shifting coefficient highly affects the shape of distribution, it receives less attention in the literature and in fact, mainstream analytical method based on backward or forward difference will lead to considerable deviations to its value. In this Letter, we show that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…bookmarks, music, movies), as well as the underlying mechanisms. Despite many previous studies demonstrated that both exponential and power-law degree distribution could be obtained by corresponding models, empirical analysis of some online bipartite networks shows that the user degree distribution actually follows shifted power-law, so-called Mandelbrot law [51,52], instead of purely exponential or power-law decay, while the object degree distribution always obeys power-law [19,50], and it can not be fully explained by previous models. Therefore, We propose an evolutionary model to consider the proactive selection activity of users and the passive pattern of objects.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…bookmarks, music, movies), as well as the underlying mechanisms. Despite many previous studies demonstrated that both exponential and power-law degree distribution could be obtained by corresponding models, empirical analysis of some online bipartite networks shows that the user degree distribution actually follows shifted power-law, so-called Mandelbrot law [51,52], instead of purely exponential or power-law decay, while the object degree distribution always obeys power-law [19,50], and it can not be fully explained by previous models. Therefore, We propose an evolutionary model to consider the proactive selection activity of users and the passive pattern of objects.…”
Section: Introductionmentioning
confidence: 94%
“…From Eq. 12, we know that the user degree distribution is a shifted power-law distribution [53,54], which is also familiar as Mandelbort law [51,52].…”
Section: User Degree Distributionmentioning
confidence: 99%
“…In fact, strict power-law distribution is rarely observed in empirical studies albeit bursts and heavy tails are widespread. In addition to the widespread bimodal distribution, human activity patterns may be power-law distribution followed by distinct cutoff [10,[27][28][29][30], multimodal distribution of power-law with different scaling exponents [30][31][32][33], in some instances it is more consistent with Mandelbrot distribution [34], and so on. Human activity patterns exhibit such a wealth of statistical properties.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the origins of such Mandelbrot law, Ren, Yang and Wang [11] proposed a interesting growing network that is generated with linear preferential attachment. In such networks, there exits a recursive dependence relationship between every two consecutive degrees…”
mentioning
confidence: 99%
“…To derive the asymptotic of the degree distribution, Ren, Yang and Wang [11] studied the following three kinds of approximations: I) forward-difference approximation, assuming…”
mentioning
confidence: 99%